Quality Study of Activated Carbon/TiO2 Composite Based on Activated Carbon Granule Size - Mega Nurhanisa; Dwiria Wahyuni; Ya' Muhammad Arsyad (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2025)
Activated carbon (AC) composited with TiO2 photocatalyst can be used as a material that can purify wastewater. This research aims to obtain the optimum particle size of AC as a buffer for AC. The work began by making AC from oil palm empty fruit bunches (OPEFB) waste with various particle sizes, namely 50 mesh, 100 mesh, 150 mesh, and 200 mesh. AC was synthesized by carbonizing the raw materials at 500 °C and then activated using a microwave oven at 500 watts for 15 minutes. Furthermore, AC/TiO2 composites were synthesized using a microwave oven under similar conditions. Spectroscopy Electron Microscopy (SEM) characterization was done to see the morphology of AC and AC/TiO2 composites. To determine the performance of AC and AC/TiO2 composites, the degradation process of methylene blue (MB) solution was carried out. Characterization with a UV-Vis spectrophotometer was done as a quantitative method to measure the level of MB degradation. The results of MB degradation for 6 hours of irradiation showed that 200 mesh particles achieved the highest efficiency of 86.19%. Thus, using TiO2 has been shown to improve the performance of AC, with those of 200 mesh degrading MB the most.